Explaining Service-Price Differences in International Comparisons - Falvey, Rodney E.; Gemmell, Norman (American Economic Review, 1991)
This paper reexamines observed international differences in the price of services and the positive correlation of these with per capita GDP differences. Using a general trade model with a nontraded sector, we find that differences in countries' factor endowments, populations, trade policies, and trade balances will have ambiguous and sometimes opposite effects on their service prices and real incomes. Estimating the service-price equation using recent data suggests that larger endowments of agricultural land, minerals, and capital, larger trade deficits, and higher prices for tradables increase service prices. Conversely, larger populations and labor forces reduce service prices.